2010
DOI: 10.1002/dat.20488
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolitis obliterans organizing pneumonia in renal transplant patients

Abstract: Bronchiolitis obliterans organizing pneumonia (BOOP) is a syndrome with distinct clinical, radiological, and histological features. The radiographic changes of BOOP vary from multiple patchy, alveolar, or ground‐glass infiltrates to diffuse reticulonodular opacities. The most frequently observed CT features are areas of lung consolidation and ground‐glass opacity often with a subpleural distribution and small nodules; in addition, bronchial wall thickening and bronchodilatation can be seen. The exact pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[ 10 ] and Hasni et al . [ 11 ] In other cases, sirolimus was the probable agent implicated in the occurrence of organizing pneumonia. [ 12 13 14 15 ] Recovery in these cases required discontinuation of sirolimus and escalation of steroid doses.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] and Hasni et al . [ 11 ] In other cases, sirolimus was the probable agent implicated in the occurrence of organizing pneumonia. [ 12 13 14 15 ] Recovery in these cases required discontinuation of sirolimus and escalation of steroid doses.…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have reported a high rate of discontinuation secondary to side effects after the introduction of this drug [ 5 , 6 , 7 ]. Among them, pneumonitis or interstitial lung disease with a range of pulmonary histopathologic changes (including alveolar hemorrhage, pulmonary alveolar proteinosis, focal fibrosis, bronchiolitis obliterans organizing pneumonia) have been largely reported in clinical records and they have been associated with worsened patients’ clinical outcomes and drug discontinuation [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The incidence of this complications is 2–11%, frequently reported between 1 and 51 months after the beginning of mTOR inhibitor therapy [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%